Parkinsonism and cerebrospinal fluid disorders - Youn, Jinyoung; Todisco, Massimiliano; Zappia, Mario; Pacchetti, Claudio; Fasano, Alfonso (Journal of the neurological sciences, 2022)
Although various motor manifestations can be seen in patients with cerebrospinal fluid (CSF) disorders, such as hydrocephalus or intracranial hypotension, the clinical presentation with parkinsonism is not clearly elucidated. We searched the literature for studies describing the occurrence of parkinsonism in subjects with normal pressure hydrocephalus (NPH), obstructive hydrocephalus, and intracranial hypotension. We analyzed the clinical presentation (particularly with respect to bradykinesia, rigidity, rest tremor, and gait disturbance/postural instability) as well as the response to treatment. Parkinsonism was most commonly reported in NPH patients. Although gait disturbance/postural instability is a well-known motor symptom of NPH, other cardinal signs include upper limb involvement or asymmetric presentation. As for obstructive hydrocephalus, parkinsonism was mainly observed in subjects with aqueductal stenosis and more often after shunt surgery. Patients with NPH or obstructive hydrocephalus rarely improved with levodopa therapy, while most subjects only improved with shunt surgery. Although the mechanism is still controversial, a functional involvement of nigrostriatal pathway has been hypothesized based on imaging studies and case reports. Brain imaging is also helpful for atypical cases of intracranial hypotension presenting with parkinsonism. Parkinsonism improved after treatment in such cases as well. Studies exploring the relationship between CSF disorders and parkinsonism are mainly descriptive and their quality is generally poor. However, considering that these disorders can be treated, clinicians' awareness of the differential diagnosis is important and future studies better exploring the underlying pathophysiological mechanisms are warranted. This article is part of the Special Issue "Parkinsonism across the spectrum of movement disorders and beyond" edited by Joseph Jankovic, Daniel D. Truong and Matteo Bologna. •The occurrence of parkinsonism in CSF disorders is not fully elucidated.•We searched the literature for studies describing such occurrence.•Parkinsonism is most commonly reported in NPH patients.•Future studies better exploring the underlying pathophysiological mechanisms are warranted.